A psycho-spiritual life of the ego: an Iqbalian perspective - Abdul Razak, Mohd Abbas; Hanif, Syed Sikandar Shah; Abdurrahman, Muhammad AR (2020)
Over the centuries many great minds regardless in the East or West were preoccupied in the investigation on human nature and personality. Despite the existence of divergent theories on man in the West, quite a sizable number of biologists, psychologists and others who have influenced by the Darwinian Theory of evolution concluded that man is nothing more than an extension from the ape family. Yet others felt that is no connection between the body and mind. Some just believed in the mechanistic nature of the human brain in processing information at the expanse of rejecting the existence of the mind concept in man. While in the Freudian context the human psyche is divided into three warring parties; namely the Id, Ego and Superego. On the overall, the entity of the human soul has been rejected by mainstream psychologies in the West for the obvious reason that it is invisible/non-observable and intangible. In the maze of an ongoing debate in many areas of knowledge as to whether man is just made up of body or body-mind and soul, this paper intends to investigate Iqbal’s ideas on the life of the human ego. Particularly, the researchers are interested in investigating Iqbal’s ideas on man, the nature of the ego and the stages it has to journey in life before it reaches a state of immortality. During the course of writing the paper, the research team would make some sparing comparison to the Freudian concepts on human nature and personality. As a qualitative study, the research team would refer to Iqbal’s ideas present in his philosophical writings and poetry. Data related to the research will be collected from print and internet sources. The textual and content-analysis methods will be employed in interpreting the relevant data.